Using PRAAT for Analysing Segmental Features of Speech Produced by the Students of English Study Program of Universitas Brawijaya - Wulandari, Istiqomah; Rodliyah, Iis Nur; Fatimah, Fatimah (ELTICS : Journal of English Language Teaching and English Linguistics, 2016)
Making improvements of the speech feature is possible to do because pronunciation is teachable. Some experts in pronunciation teaching have suggested more comprehensive and contemporary teaching methods and techniques. In narrower context to English Study Program some seemingly cases are found in depicting the condition of how the last semester students who attend thesis seminar are tend to have difficulty in their Pronunciation. Many of them are still struggling in articulating the correct English pronunciation. The problematic speech features are targeted to the segmental part, such as the accuracy of vowel sounds production. For this particular research, the researchers want to investigate the similar problematic features of pronunciation of the second semester students of English Study Program of Universitas Brawijaya and later will try to implement some teaching pronunciation techniques to modify their pronunciation production. For this particular research employs a qualitative research design. The data were analysed into narrative description, interpretation and textual. The participants were asked to read aloud the given 14 minimal pair words list. The recorded data were saved as wave files (.wav) to analyze them by using PRAAT to visual display of the students’ First Formant (F1) and Second Formant (F2). Then, these visual displays were compared to those of native speakers in PRAAT window. The result of this research reveals that due to the lack of how to disambiguate the correct pronunciation of vowel sounds within the given words the participant tend to produce inaccurate pronunciation. Which are reflected by the result of the spectrum score range: F1 and F2. Some proposed techniques of teaching segmental were drilling, teaching minimal pairs, chanting with jazz chant and rhyming with tongue twisters, to modify learners segmental features. As the suggestion all targeted parties (students, Lectures and Authority) should be willing to do what are necessary to maintain the success of the teaching and learning pronunciation in Study program of English.Key words: student’ spoken feature, segment